Identification and characterization of Drosophila genes for synaptic vesicle proteins - DiAntonio, A (J Neurosci, 1993)
Proteins associated with synaptic vesicles are likely to control the release of neurotransmitter. Because synaptic transmission is fundamentally similar between vertebrates and invertebrates, vesicle proteins from vertebrates that are important for synaptic transmission should be present in Drosophila as well. This investigation describes Drosophila homologs of vamp, synaptotagmin, and rab3 that are expressed in a pattern consistent with a function in Drosophila neurotransmission. One previously reported candidate (syb), a Drosophila homolog of the vamp or synaptobrevin proteins, has been shown to be expressed at very low levels in neurons and is most abundant in the gut. A neuronal Drosophila vamp (n-syb) is described here and is localized to chromosome band 62A. Northern analysis and in situ hybridizations to mRNA indicate that the novel vamp, as well as the genes for synaptotagmin (syt) and rab3 (drab3), is expressed in the Drosophila nervous system. These genes are widely (perhaps ubiquitously) expressed in the nervous system and we have no evidence of additional neuronal isoforms of synaptotagmin, vamp, or rab3. Immunoreactivity for synaptotagmin and vamp is located in synaptic regions of the nervous system. This distribution suggests that these molecules are components of synaptic vesicles in Drosophila. The conserved structure and neuronal expression pattern of these genes indicate that they may function in processes that are required for both vertebrate and invertebrate synaptic transmission. Because of their distribution in the nervous system and because n-syb, synaptotagmin, and drab3 do not appear to be in a family of functionally redundant homologs, we predict that mutation of these genes will have a profound neurological phenotype and that they are therefore good candidates for a genetic dissection in Drosophila.